Transit-oriented development for older adults: A survey of current practices among transit agencies and local governments in the US - Duncan, Michael; Gladwin, Kristin; Wood, Brittany; Valdez Torres, Yazmin; Horner, Mark (Journal of Transport and Land Use, 2021)
This study seeks to examine the ways in which transit agencies and local governments have been considering the transportation needs of older adults when planning for transit-oriented development (TOD). Surveys with representatives from a sample of transit agencies (n= 15) and local governments (n=31) from across the US were conducted. Few of the surveyed agencies indicated that they had specific practices that encourage TOD to help meet the transportation needs of older adults. Respondents identified the cost of development, market forces, and the lack of specific amenities for older adults as the primary barriers to attracting aging groups to TOD.